آليات حماية حرية الإعلام في القانون الدولي (مجلة الواحات للبحوث والدراسات, 2015)
The International human rights law has included  a series of laws to ensure adequateprotection of journalists from being harmed  when they are practicing their duties ,as well as the protection of media with cases of war and peace, And it considered the work of the journalist  is one of the fundamental human rights and the report of liberty of press, opinion and media in all its forms in order to enable them to defend from themselves and to provide a special protection to men of media because of the specificity of their profession. And this has been stated in various ,global , and international and regional instruments. Such as the Universal Declaration of Human Rights (AD 19) and the International Covenant on Civil and Political Rights (CG 19.Also , it included the  international humanitarian law because it is a part of the international human rights law in order to ensure the protection of journalists in cases of armed conflicts as civilians , and to  protect them from any form of attacks with the of their non participation in hostilities, and to consider building  and equipment of media as civilian objects which shall not be the object of attacks or reprisals.